Street-Fighting Mathematics : The Art of Educated Guessing and Opportunistic Problem Solving - Mahajan, Sanjoy, 1969- (Book collections on Project MUSE., 2010)
"In Street-Fighting Mathematics, Sanjoy Mahajan builds, sharpens, and demonstrates tools for educated guessing and down-and-dirty, opportunistic problem solving across diverse fields of knowledge - from mathematics to management. Mahajan describes six tools: dimensional analysis, easy cases, lumping, picture proofs, successive approximation, and reasoning by analogy. Illustrating each tool with numerous examples, he carefully separates the tool - the general principle - from the particular application so that the reader can most easily grasp the tool itself to use on problems of particular interest." "Street-Fighting Mathematics grew out of a short course taught by the author at MIT for students ranging from first-year undergraduates to graduate students ready for careers in physics, mathematics, management, electrical engineering, computer science, and biology. They benefited from an approach that avoided rigor and taught them how to use mathematics to solve real problems."--Jacket.